2012
DOI: 10.1016/j.explore.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

How Might Yoga Help Depression? A Neurobiological Perspective

Abstract: Depression is a prevalent mental health condition worldwide and is the leading cause of disability in adults under the age of 45. Most individuals with major depressive disorder (MDD) report only a 50% decrease in symptoms with the use of the standard allopathic treatments for depression. The mechanisms underlying depression remain poorly understood even though stress and its correlates contribute to multiple aspects of the phenomenology of depression. Thus, stress and depression are clearly linked, as stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 88 publications
0
75
0
5
Order By: Relevance
“…Trauma-informed yoga has been shown to mitigate stress responses via both botom-up (accessing the primitive brain and emotions) and top-down (psychological reappraisal) methods. Top-down cortically mediated techniques can be harnessed to observe and facilitate sensorimotor processing [56]. Controlled studies have demonstrated that certain "yoga practices decrease symptoms in PTSD, obsessive compulsive disorders, generalized anxiety disorder, panic disorder and anxiety after natural disasters…reducing the stress-induced allostatic load in the autonomic nervous system," [57] It has also been reported that in yoga practitioners, brain volume is larger in areas that: contain a mental map of the body, direct atention, control vision, reduce stress, and deine the concept of self [58].…”
Section: Trauma-informed Yogamentioning
confidence: 99%
“…Trauma-informed yoga has been shown to mitigate stress responses via both botom-up (accessing the primitive brain and emotions) and top-down (psychological reappraisal) methods. Top-down cortically mediated techniques can be harnessed to observe and facilitate sensorimotor processing [56]. Controlled studies have demonstrated that certain "yoga practices decrease symptoms in PTSD, obsessive compulsive disorders, generalized anxiety disorder, panic disorder and anxiety after natural disasters…reducing the stress-induced allostatic load in the autonomic nervous system," [57] It has also been reported that in yoga practitioners, brain volume is larger in areas that: contain a mental map of the body, direct atention, control vision, reduce stress, and deine the concept of self [58].…”
Section: Trauma-informed Yogamentioning
confidence: 99%
“…examined the mechanism of action of yoga [7,[11][12][13] have come very close to articulating the missing causal pathway. However, neither ancient literature nor modern scholarship has explicitly identified the foundational premise, leaving scope for general misinterpretation.…”
Section: Journal Of Yoga and Physiotherapymentioning
confidence: 99%
“…Kinser et al expound neurobiological mechanisms of yoga. Their model elaborates on various neurobiological substrates or circuits in order to explain how yoga works [12]. Similarly, Streeter et al base their theory on neurophysiology and suggest that yoga reduces allostatic load in the stress response system [18].…”
Section: Current Research In Mechanism Of Action Of Yogamentioning
confidence: 99%
“…However, individuals with depressive symptoms have reduced self-regulation and self-efficacy related to PA and report great difficulty following-through with PA behaviors [47,48]. Negative perseverative self-talk (ruminations), a hallmark symptom of depression in women, can lead to further Yoga for depression in pregnancy 5 reductions in PA and reinforce already low levels [49,50]. This is problematic because a depression-related sedentary lifestyle during pregnancy is associated with continued depressive symptoms, risk for poor pregnancy outcomes, and additional chronic illness [51].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, yoga provides an opportunity to be mindful of symptoms and adapt the practice according to those symptoms; for example, specific gentle breathing practices and movements may be advisable when one is experiencing predominantly depressive symptoms (e.g., lethargy, anhedonia) and others are more appropriate when anxious symptoms are predominant (e.g., ruminations) [50,56,70].…”
Section: Introductionmentioning
confidence: 99%